PENAFSIRAN EMANSIPATORIS DALAMAL-QUR’AN (PERSPEKTIF PEMIKIRAN NASARUDDIN UMAR) - Nella Lucky (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
As implication of spirit that quran shalihun likulli zaman wamakan an interpreter try to make middle part interpretation which full of values truely states in al quran. Such as justice, peace, etc. Text in al quran always connectedwith social part. The reader has differences in understanding. Because of that text has completely content and possible that there are a lot of approaching which is inter-multidisipliner. One of them is using gender approaching in analizing and it is done Indonesia mufassir it self. Nasarudiin umar try to give new colour in interprete al quran. He share etimology analize, hermeneutic and use history to research many words in al quran. See the macro socio aspect either micro culture which arround the text. Its a truth that all aspects about women issues based on al quran interpretation.